2006
DOI: 10.1111/j.1398-9995.2005.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic diseases and atopic sensitization in children related to farming and anthroposophic lifestyle – the PARSIFAL study

Abstract: This study indicates that growing up on a farm, and to a lesser extent leading an anthroposophic life style may confer protection from both sensitization and allergic diseases in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
244
4
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(259 citation statements)
references
References 24 publications
4
244
4
7
Order By: Relevance
“…The etiological mechanisms are unclear, but probiotic bacteria or other currently unidentified non-microbial components in farm milk may play a role. Evidence from other populations with anthroposophic lifestyles, which are characterized by (among other things) diets rich in (probiotic) microbes [58], suggests that this protective effect may not be limited only to the farming environment; however, results have not always been consistent [59]. Similar to the recent 'rediscovery' of Blackley's observation of the protective farming environment, the idea that probiotic bacteria may affect the immune system and have beneficial effects on human health was first proposed more than a century ago by a contemporary of Blackley, the Russian Nobel-prize laureate Elias Metchnikoff [60].…”
Section: Protective Exposuresmentioning
confidence: 88%
See 1 more Smart Citation
“…The etiological mechanisms are unclear, but probiotic bacteria or other currently unidentified non-microbial components in farm milk may play a role. Evidence from other populations with anthroposophic lifestyles, which are characterized by (among other things) diets rich in (probiotic) microbes [58], suggests that this protective effect may not be limited only to the farming environment; however, results have not always been consistent [59]. Similar to the recent 'rediscovery' of Blackley's observation of the protective farming environment, the idea that probiotic bacteria may affect the immune system and have beneficial effects on human health was first proposed more than a century ago by a contemporary of Blackley, the Russian Nobel-prize laureate Elias Metchnikoff [60].…”
Section: Protective Exposuresmentioning
confidence: 88%
“…A related issue is that a number of studies have found consistently low prevalences of allergies and asthma in farmers' children, both in high-income countries such as Canada, the USA, Australia, New Zealand and Europe [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and in lowincome countries including Mongolia and Southern Africa [21,22]. These protective effects for allergies and asthma have also been observed in adult farmers [23][24][25][26][27][28][29][30][31][32][33][34][35][36], despite the increased risks of other respiratory conditions, such as chronic obstructive pulmonary disease, reduced lung function and farmers' lung [37].…”
mentioning
confidence: 99%
“…This suggests that the protective effects of early life exposures may eventually wear off. Numerous studies demonstrated lower odds of AD and allergic disease in farm and rural children, though the inverse associations were more consistent for respiratory atopy [67,68]. The protective effects may be related to exposure to manure and microbial exposure in the home [68,69].…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…Children growing up on small dairy farms have a remarkably low incidence of allergy compared with other children growing up in rural environments, but not on a farm [13]. Frequent contact with livestock and fodder [4] and consumption of unpasteurized milk [5] have been associated with protection.…”
Section: Introductionmentioning
confidence: 99%